Effect of banana bunch covering technology for quality banana production in Bangladesh - Rubel, MHK; Hossain, MM; Hafiz, MMH; Rahman, MM; Khatun, MR (Progressive Agriculture, 2020)
This study was carried out at Horticulture farm of Bangladesh Agricultural University, Mymensingh in order to find out the effects of bunch covering materials on physio-morphological characters and shelf life of banana cv. Mehersagar. The experiment was undertaken during the period from July to November 2016 with four types of bunch covering materials namely white polythene bag, black polythene bag, blue polythene bag and old cloth along with control (no bunch covering). The experiment was laid out in randomized complete block design with five replications. The results of the investigation revealed that blue polythene bag required significantly minimum days to harvest (76.80 days) and maximum days to harvest (97.80 days) were recorded for control. Maximum bunch weight (19.90 kg), finger length (19.59 cm) and finger diameter (3.56 cm) were recorded for blue polythene bag whereas control showed minimum bunch weight (15.20 kg), finger length (14.57 cm) and finger diameter (3.07 cm). It was observed that blue polythene bag covered fruits showed minimum disease infection (2.33%), insect infestation (2.33%) and physiological disorder (1%) compared to control which experienced maximum disease infection (12.67%), insect infestation (50%) and physiological disorder (13.40%). Weight loss (11.18%), pulp moisture (66.16%), peel moisture (70.41%), disease infection (40%), disease severity (70.25%), skin colour change (4.95) were also lower in blue polythene bag than non covering control fruits. The bunches covered with blue polythene bag exhibited superior results in respect of pulp thickness (3.45cm), pulp to peel ratio (2.49), pulp dry matter (33.84%), peel dry matter (29.59%), TSS (24.28 % Brix), shelf life (11.40 days) than the rest of bunch covering materials used in this study. It can be concluded that bunch covering showed significant effect on physio-morphological traits and quality of banana. Progressive Agriculture 30 (3): 238-252, 2019